2006
DOI: 10.1590/s1413-78522006000100010
|View full text |Cite
|
Sign up to set email alerts
|

Dor no ombro em pacientes com lesão medular

Abstract: A lesão medular (LM) é uma das formas mais graves dentro das síndromes incapacitantes. O paciente com LM sobrecarrega excessivamente os membros superiores, especialmente os ombros, utilizando-os mais freqüentemente e em maior variabilidade de atividades que uma pessoa sem LM. Além disso, a busca da melhoria da qualidade de vida nos últimos anos, levou um número crescente de portadores de LM a procurar a prática de atividade física. Muitos pacientes com LM utilizam cadeira de rodas para locomoção funcional e re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Shoulder pain is known to be prevalent in patients with SCI, and Rotator cuff problems were frequently identified [31][32][33]. Previous studies showed that shoulder pain is primarily caused by an excessive overload on the upper limbs, such as wheelchair propulsion and transfers [32,34]. This overuse of the shoulder muscles could lead to degenerative conditions of the shoulders [33].…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder pain is known to be prevalent in patients with SCI, and Rotator cuff problems were frequently identified [31][32][33]. Previous studies showed that shoulder pain is primarily caused by an excessive overload on the upper limbs, such as wheelchair propulsion and transfers [32,34]. This overuse of the shoulder muscles could lead to degenerative conditions of the shoulders [33].…”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, due to the need of the sitting position, many daily activities need to be performed with the arm above the head, resulting in muscle imbalance and overload. 15 This overload affects one joint not designed to withstand such loads and possibly presents a muscle imbalance depending on the level of injury, resulting in pain and further, some degree of joint destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is acromioclavicular stabilization solicited by the mechanical overload during transfer, but this action can also intermittently reduce the subacromial space, determining compression of the rotator cuff structures, especially of the suprascapularis muscle 28 . The recurrent compression can lead to hypovascularization besides mechanical stress on the muscle fiber due to micro strains.…”
Section: Discussionmentioning
confidence: 99%